Actualizing The Nationalism Attitude of Millennial Generation Towards Pancasila and Citizenship Education in The Digital Era - Siti Maizul Habibah; Salsabila Maharani; Riska Hilshcer (Jurnal Civicus, 2023)
This study aims to identify the causes of the decline in nationalism in the millennial generation and find effective ways to awaken and maintain this nationalism through Pancasila and civic education, as well as the role of education, family and government. The research method used is literature study using sources such as books, journals, and internet media articles. The results of this study reveal that the decline in nationalism in the millennial generation is caused by two factors, namely internal factors and external factors. Internal factors include feelings of disappointment, for example towards the government's performance in managing various legal processes. External factors related to the influence of globalization and modernization. To grow and maintain an attitude of nationalism in the millennial generation, this can be done through the use of technology as a means of conveying information, providing an understanding of the importance of nationalism through Pancasila and citizenship education, and preserving regional culture.